Observe the follwing 6 6 2 6 6 6 2 6 6 6 6 2 = 4 3 5 6 = 4 4 3 5 5 6 = 4 4 4 3 5 5 5 6 Is it true that 6 6 6 ⋯ 6 6 2 n 6’s = 4 4 4 ⋯ 4 n-1 3’s 3 5 5 5 ⋯ 5 5 n-1 6’s 6 ?
This is an original problem .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Sir @Pi Han Goh . Can you check it out please? Let me know whether the working is rigorous or not. I would be glad to make it error free
Log in to reply
It would better to explain what this sequence of numbers, a 0 , a 1 , … represent.
Plus, I know what you're trying to say, but why do you have ( a 0 , a 1 , a 2 ) = ( 8 1 , 8 0 1 , 8 0 0 1 ) first, then later you have ( a 0 , a 1 , a 2 ) = ( 8 9 , 8 8 9 , 8 8 8 9 ) ? It's important to have a consistent use of notations.
While I noticed that you have used induction twice, why don't you just use it once? That is,
For positive integer n ≥ 2 , let A n = ( n times 6 6 6 6 … 6 ) 2 . We can use induction to prove that A n = that same expression .
How? Show that A n × 1 2 1 = A n + 1 . Use long multiplication, and you're done.
Problem Loading...
Note Loading...
Set Loading...
Call the number A = 6 6 6 ⋯ 6 6 6 having n numbers of sixes. Now A 2 = ( n 6’s 6 6 6 ⋯ 6 6 6 ) 2 = 3 6 ( 9 1 0 n − 1 ) 2 = 9 4 ( 1 0 2 n − 2 ⋅ 1 0 n + 1 ) Since 1 0 2 n − 2 ⋅ 1 0 n = 1 0 n ( 1 0 n − 2 ) = 1 0 n ( n-1 9’s 9 9 9 ⋯ 9 8 ) = n-1 9’s 9 9 9 ⋯ 9 8 n 0’s 0 0 0 ⋯ 0 Therefore We have the following B = 1 0 2 n − 2 ⋅ 1 0 n + 1 = n-1 9’s 9 9 9 ⋯ 9 8 n -1 0’s 0 0 0 ⋯ 0 1 = n-1 9’s 9 9 9 ⋯ 9 0 + 8 n -1 0’s 0 0 0 ⋯ 0 1 Let a 0 = 8 1 and observe that a 1 = 8 0 1 = 7 2 0 + 8 1 = 7 2 0 + a 0 , a 2 = 8 0 0 1 = 7 2 0 0 + 8 0 1 = 7 2 0 0 + a 1 and ∀ n ≥ 2 we have following recursive formula (by induction can be proved) a n − 1 = 7 2 × 1 0 n − 1 + a n − 2 which when divided by 9 gives R = k = 1 ∑ n − 1 8 ⋅ 1 0 k + 9 = n-1 8’s 8 8 ⋯ 8 9 Thus we prove 9 B = n-1 1’s 1 1 ⋯ 1 1 0 + n-1 8’s 8 8 ⋯ 8 9 and further multiplying gives 9 4 B A 2 = n-1 4’s 4 4 ⋯ 4 4 0 + 3 n-1’s 5 5 ⋯ 5 5 6 = ( n 6’s 6 6 6 ⋯ 6 6 6 ) 2 = n-1 4’s 4 4 ⋯ 4 4 3 n-1 5’s 5 5 ⋯ 5 5 6 Proof for 4 × n-1 8’s 8 8 ⋯ 8 9 = 3 n-1 5’s 5 5 ⋯ 5 5 6 If a 0 = 8 9 then a 1 = 8 8 9 = 8 0 0 + a 0 , a 2 = 8 8 8 9 = 8 0 0 0 + a 1 Giving us the recursive formula ∀ n ≥ 2 ( by induction can be proved ) a n − 1 = 8 ⋅ 1 0 n − 1 + a n − 2 and hence 4 a n − 1 = 3 2 ⋅ 1 0 n − 1 + 4 a n − 2 = k = 1 ∑ n − 1 3 2 ⋅ 1 0 k + 3 6 = 3 n-1 5’s 5 5 ⋯ 5 5